Development of A Loop-Mediated Isothermal Amplification (LAMP) Assay for Detection of Relapsing Fever Borreliae - Faezeh Houmansadr; Mohammad Soleimani; Saied Reza Naddaf (Tehran University of Medical Sciences, 2019)
Background: This study aimed to develop a loop-mediated isothermal amplification (LAMP) assay for the rapid detection of tick-borne relapsing fever in resource-limited areas. Methods: A set of six primers were designed based on the conserved regions of the Glycerophosphodiester phosphodiesterase (glpQ) gene of Borrelia species. For sensitivity assay, serial dilutions of a recombinant plasmid containing a 219bp sequence of the glpQ were prepared and used as the template DNA. The LAMP reactions containing the six primers and the reagents required for amplification were incubated at 60-65 °C for 60min in a Loopamp real-time turbidimeter. For the specificity test, DNA from 14 other bacteria were included in the assays, and double-distilled water was used as the negative control. Also, DNA from dried blood spots (DBSs) of spirochetemic mice, and blood samples from relapsing fever-suspected patients were examined by the LAMP along a Borrelia-specific nested PCR that targets the rrs-rrl-IGS region. Results: The LAMP detected as low as 90glpQ copies in reactions. The primers reacted with DNA from DBS of spirochetemic mice showing spirochete concentrations of ≤ one per a 1000X microscopic field. In clinical samples, the LAMP assay showed a higher sensitivity compared to nested-PCR. The LAMP specificity was 100%, as the primers did not react with other bacteria DNA. Conclusion: The high sensitivity and specificity of the test, along with the simplicity of the DNA extraction procedure, make the LAMP a reliable and adaptable tool for the diagnosis of tick-borne relapsing fever in rural endemic areas.